2016
DOI: 10.1002/ps.4410
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of plant‐provided food supplements on pest consumption by omnivorous predators: lessons from two coccinellid beetles

Abstract: For these two predators, the tested pollen serves as an essential supplement to a diet of prey. However, the benefit of a mixed prey-pollen diet was not always sufficient to overcome individual decrease in pest consumption. Taken together, our study highlights the importance of addressing both positive and negative roles of plant-provided food supplements in considering the outcome for biological control efforts that rely on omnivorous predators. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…The higher number of coccinellids in traps in NFS than in avocado orchards could be due to the provision of nectar, pollen, prey resources, or a combination of these, particularly in summer and autumn, given that these are alternative or complementary resources commonly consumed by coccinellids (Lundgren, 2009a, b;Hodek & Evans, 2012). Pollen has been described as one of the most nutritious alternative food for coccinellids (Lundgren, 2009a, b), and for H. variegata, one of the most common species found in our samplings, pollen has been described as an important resource for larval development (Schuldiner-Harpaz & Coll, 2017). Thus, flower strips with complementary flowering times could represent a more constant food resource year-round.…”
Section: Discussionmentioning
confidence: 77%
“…The higher number of coccinellids in traps in NFS than in avocado orchards could be due to the provision of nectar, pollen, prey resources, or a combination of these, particularly in summer and autumn, given that these are alternative or complementary resources commonly consumed by coccinellids (Lundgren, 2009a, b;Hodek & Evans, 2012). Pollen has been described as one of the most nutritious alternative food for coccinellids (Lundgren, 2009a, b), and for H. variegata, one of the most common species found in our samplings, pollen has been described as an important resource for larval development (Schuldiner-Harpaz & Coll, 2017). Thus, flower strips with complementary flowering times could represent a more constant food resource year-round.…”
Section: Discussionmentioning
confidence: 77%
“…La ingesta de polen por coccinélidos puede aumentar su longevidad y fecundidad (Lundgren, 2009), pero las dietas mixtas especialmente con polen, son las más adecuadas para su desarrollo (Nielsen et al, 2002;Schuldiner-Harpaz & Coll, 2017), que solo el consumo de áfidos o de huevos de lepidópteros (Sayed & El Arnaouty, 2016). El polen además de proporcionar nutrientes (Patt et al, 2003), puede contener compuestos que estimulan la ingesta del depredador (Berkvens et al, 2008), pero también producir tasas de desarrollo y reproducción reducidas (Lundgren, 2009;Sayed & El Arnaouty, 2016).…”
Section: Discussionunclassified
“…For instance, Bertrand et al [ 56 ] reported that two generalist predators of crop aphids (a ladybeetle species: H. axyridis , and a lacewing species: Chrysoperlacarnea ) could utilize pollen sources from trees (e.g., Salix , Prunus , Quercus , and Acer ) to survive during seasonal shifts in resources in agricultural landscapes. Plant-provided food supplements can affect diversity and biological pest control by omnivorous predators [ 57 ]. Some non-crop plants could attract and conserve aphid predators in specific crop fields [ 58 ], and plant morphology may affect ladybeetle mobility, foraging behavior, and access to prey, encouraging them to forage on preferred plant types [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%